Language and Gender Representation in Corporate Social Responsibility: A Case Study of PT Kideco’s Company Profile - Muhammad Khaidirr Nasik; Wilma Prafitri (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
Corporate Social Responsibility discourse serves as a key platform for gender representation in Indonesia's male-dominated mining sector. This study examines linguistic gender patterns in PT Kideco Jaya Agung's Company Profile 2024 using Fairclough's (1992) three-dimensional Critical Discourse Analysis framework. Manual analysis identified 70 gender references across 45 pages, revealing "pria" dominance at 67.1% (47 instances) versus 32.9% female terms (23 instances), despite the company's reported 15% female workforce participation. Key findings demonstrate 69.6% of female references employ passive constructions compared to 27.7% of male references, positioning women as beneficiaries rather than operational agents. Collocational analysis shows male terms associated with core functions (operations, leadership) while female terms cluster around peripheral social programs (training, empowerment), evidencing tokenistic discourse despite numerical diversity achievements. These patterns confirm persistent patriarchal framing characteristic of mining CSR communication. The study recommends gender-neutral terminology, active voice constructions, and balanced collocational representation to achieve linguistic equity. Findings contribute methodological insights for analyzing corporate gender discourse in extractive industries. Keywords: CSR discourse, gender representation, critical discourse analysis, mining industry, linguistic asymmetry